A 'strategy of resistance'? How can a place-based empowerment programme influence local media portrayals of neighbourhoods and what are the implications for tackling health inequalities?. (May 2020) - Halliday, Emma; Collins, Michelle; Egan, Matthew; Ponsford, Ruth; Scott, Courtney; Popay, Jennie
Abstract: Place-based stigma is linked with health and social harms, but few studies have assessed what actions may reduce these. Area-based programmes are one potential strategy but may exacerbate stigma by targeting disadvantaged neighbourhoods. We reviewed newspaper coverage in two stigmatised neighbourhoods to identify whether a programme funded in these localities influenced reporting. While both areas were dominated by negative coverage, the progamme provided an impetus for some positive stories over time and enabled community activists to articulate alternative narratives about where they lived, countering negative external portrayals. The involvement of residents should be central to strategies to tackle place-based stigma. Highlights: Explores how two stigmatised places in England were portrayed in local newspapers. Found that negative reporting (e.g. crime) dominated coverage of both areas. The programme enabled residents to have a voice in shaping more positive local news coverage.